Wi-Fi Login Authentications System Using MikroTik - Khairuddin, Abdul Mu'im Azraei; Bahari, Azlina (Progress in Engineering Application and Technology, 2023)
The Wi-Fi Login Authentications System Using MikroTik aims to create a customized login portal for users accessing a MikroTik hotspot. MikroTik hotspots are a popular and widely used solution for providing wireless internet access in public places such as coffee shops, hotels, and airports. The current login process for MikroTik hotspots is often viewed as a cumbersome and unappealing process for users. The login page will providing a user-friendly and intuitive interface that simplifies the login process. The page will be designed with a focus on usability and accessibility, with the goal of making it easy for users to access the internet through the hotspot. The custom log-in page will include various features that are not present in the standard MikroTik hotspot log-in process. The Wi-Fi Login Authentications System Using MikroTik project will be developed using web technologies such as HTML, CSS, and JavaScript to ensure compatibility with a wide range of devices and browsers. The project will be implemented on a MikroTik router, which will serve as the gateway for all incoming and outgoing traffic. Overall, the project aims to provide a seamless and efficient user experience for those accessing the hotspot, by creating a customized log-in portal that is easy to use and offers useful features. The custom log in page will not only improve the user experience but also help to increase the number of users that sign up to the hotspot, ultimately resulting in increased revenue for the hotspot operator.